DYNAMICS OF THE INDICATORS OF LUNG DESTRUCTION AND HORMONAL BACKGROUND AS A PREDICTIVE MARKER OF THE EFFECTIVENESS OF MULTIDRUG RESISTANT TUBERCULOSIS TREATMENT - O.S. SHEVCHENKO; I.A. OVCHARENKO; O.N. SHVETS (Avicenna Tajik State Medical University, 2019)
Objective: Study of the dynamics of indicators of pulmonary tissue destruction and hormonal background, as a marker for predicting the effectiveness of treatment of multidrug resistant tuberculosis (MDR TB). Methods: The study involved 84 patients with new cases of MDR TB, which were divided into groups with effective (group I) and ineffective (group II) treatment of tuberculosis. The criteria for the effectiveness of treatment of tuberculosis were the cessation of bacterial excretion and the closed cavity destruction. Results: It was found that in patients from group I, the levels of free hydroxyproline were lower than in group II during the first two months of treatment: at the beginning of treatment by 60%, after 2 months of treatment - by 29.4%. In both groups, there was an increase in this indicator during the first 2 months of treatment. The level of protein-bound hydroxyproline was higher in group I by 21.7%. The level of aldosterone in the groups at the beginning of treatment was almost the same. After 2 months of treatment, its level decreased in both groups. However, after 2 months of treatment in group I, its content was lower than in group II by 12.7%. In the course of treatment, the insulin resistance index in patients of both groups decreased to the norm, however, it remained higher in patients of group II (2.4±1.1 vs. 1.6±0.8). At the same time the level of insulin secretion in patients with a favorable course of the disease has decreased almost three times in compared with the baseline data (7.4 vs. 20.1 μU/ml), while in the group of patients with an unfavorable course it decreased only in 2 times (10.3 vs. 22.9 μU/ml). Conclusion: The obtained data allow recommending the study of indicators of carbohydrate metabolism, the reorganization of connective tissue and aldosterone in dynamics as an early marker of effective treatment of MDR TB.